Modeling of the plywood making process glued with thermoplastic polymer - Kozak, R.O.; Kusniak, I.I. (Forestry, Forest, Paper and Woodworking Industry, 2019)
A promising variety of the wood composite materials is plywood glued with thermoplastic polymers. However, making such a wood composite requires adjustment of the pressing modes, because there is a slightly difference between the hot method of the veneer packages pressing glued with thermoplastic films and the method of the veneer packages pressing glued with thermosetting adhesives. Among the main processes that occur in the gluing plywood process are heat and mass transfer. The availability of the thermoplastic film between the veneer sheets is going to change the thermal conductivity of the package, and therefore will affect the pressing duration. If suppose, that the package has a plate appearance, which is located between heated to the certain temperature pressed plates, then the known Fourier-Kirchhoff thermal differential equation can be applied. The basis for the model development of the warming package veneer process glued with thermoplastic film are laid methods of nonlinear programming, uniform search and conjugate gradient. On the offered mathematical model basis, the temperature field change in the package thickness during the plywood gluing with plastic film is calculated, the calculation of the warming duration indicators of the package veneer is done and this indicator dependence on the thermoplastic film flow rate and the pressing temperature is established. The duration of the warming package veneer glued with thermoplastic film depends on the temperature at which the thermoplastic polymer will change from a highly elastic to the viscous state. The transition of the thermoplastic film LDPE to the viscous state begins at 125оС and lasts up to 240 оС. With increasing of the press temperature plates from 140 to 180оС the duration of warming up the middle of the package to 125оС decreases by 89% for all investigated polymer costs is established. Changing the polymer content in the package does not significantly affect the duration of its warming. With increasing of the thermoplastic film flow rate from 130 g/m2 to 190 g/m2, the duration of warming up the middle of the veneer package to 125оС increases slightly from 3,8 to 4,2% depending on the pressing temperature. Suggested mathematical model allows to set the material parameters and plywood pressing mode influence on the duration of the warming package veneer while plywood making glued with the thermoplastic film LDPE.